Recent advances in optical tweezers - Moffitt, Jeffrey R; Chemla, Yann R; Smith, Steven B; Bustamante, Carlos (Annual review of biochemistry, 2008)
It has been over 20 years since the pioneering work of Arthur Ashkin, and in the intervening years, the field of optical tweezers has grown tremendously. Optical tweezers are now being used in the investigation of an increasing number of biochemical and biophysical processes, from the basic mechanical properties of biological polymers to the multitude of molecular machines that drive the internal dynamics of the cell. Innovation, however, continues in all areas of instrumentation and technique, with much of this work focusing on the refinement of established methods and on the integration of this tool with other forms of single-molecule manipulation or detection. Although technical in nature, these developments have important implications for the expanded use of optical tweezers in biochemical research and thus should be of general interest. In this review, we address these recent advances and speculate on possible future developments.